2015
DOI: 10.7314/apjcp.2015.16.16.7139
|View full text |Cite
|
Sign up to set email alerts
|

Resistin and Insulin Resistance: A Link Between Inflammation and Hepatocarcinogenesis

Abstract: Background: Hepatocellular carcinoma (HCC) is the sixth most common cancer and the third leading cause of cancer related death overall. The role of insulin resistance in the development of HCC associated with chronic HCV infection has not been established. Resistin is a polypeptide hormone belonging to the adipokine family which could contribute to tumorigenesis and angiogenesis. Our aim was to study serum resistin and insulin resistance as risk factors for HCC in HCV cirrhotic patients. Materials and Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…While our study provides first evidence for a role of resistin in cancer chemoresistance, its role in insulin resistance is well characterized [44]. Incidentally, insulin resistance is also associated with high risk of human cancers [45], including BC [46]. …”
Section: Discussionmentioning
confidence: 99%
“…While our study provides first evidence for a role of resistin in cancer chemoresistance, its role in insulin resistance is well characterized [44]. Incidentally, insulin resistance is also associated with high risk of human cancers [45], including BC [46]. …”
Section: Discussionmentioning
confidence: 99%
“…Hyperresistinemia in patients with chronic HCV infection has been consistently reported [115][116][117][118][119]. This condition is reversed after viral clearance [55,120,121] and determines moderate to severe fibrosis [117]. Our previous study showed that resistin originates primarily from intrahepatic lymphocytes, stellate cells, Kupffer cells, hepatic progenitor cells, and hepatocytes in HCV-infected patients [120].…”
Section: Resistinmentioning
confidence: 94%
“…Although the baseline resistin level was reported to be unassociated with therapeutic response [55], fine-tuned by resisin SNPs including RETN-rs34861192, RETN-rs3219175, RETN-rs3745367, and RETN-rs1423096, the intrahepatic, multicellular resistin reinforced IFNL3 in eliminating HCV via immunomodulation [120]. Moreover, high serum resistin levels might allow early identification of patients with cirrhosis who are at substantially increased risk of HCC [121].…”
Section: Resistinmentioning
confidence: 99%
“…In patients with NASH, the serum levels of resistin also showed an inverse correlation with the stage of fibrosis [218]. High resistin levels (>12 ng/mL) were associated with HCV-related cirrhosis and are considered an independent risk factor for the development of HCV-related HCC [219]. However, the role of resistin in NASH-related HCC has not been investigated, yet.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%